2014
DOI: 10.1016/j.febslet.2014.02.041
|View full text |Cite
|
Sign up to set email alerts
|

RASSF tumor suppressor gene family: Biological functions and regulation

Abstract: a b s t r a c tGenetic changes through allelic loss and nucleic acid or protein modifications are the main contributors to loss of function of tumor suppressor proteins. In particular, epigenetic silencing of genes by promoter hypermethylation is associated with increased tumor severity and poor survival. The RASSF (Ras association domain family) family of proteins consists of 10 members, many of which are tumor suppressor proteins that undergo loss of expression through promoter methylation in numerous types … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
121
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 116 publications
(123 citation statements)
references
References 185 publications
(387 reference statements)
2
121
0
Order By: Relevance
“…Therefore, miR-214 regulates cell apoptosis through suppressing RASSF5, which inhibits FOXO3a phosphorylation and BIM expression. The exact mechanism of RASSF5 down-regulation in oral cancer remains unclear, though some other studies have demonstrated that hyper-methylation of the RASSF5 promoter might be involved in the down-regulation of RASSF5 in several cancers (Hesson et al, 2003;Volodko et al, 2014). However, the hyper-methylation of RASSF5 promoter was not measured in our study and is the main study limitation.…”
Section: Discussionmentioning
confidence: 66%
“…Therefore, miR-214 regulates cell apoptosis through suppressing RASSF5, which inhibits FOXO3a phosphorylation and BIM expression. The exact mechanism of RASSF5 down-regulation in oral cancer remains unclear, though some other studies have demonstrated that hyper-methylation of the RASSF5 promoter might be involved in the down-regulation of RASSF5 in several cancers (Hesson et al, 2003;Volodko et al, 2014). However, the hyper-methylation of RASSF5 promoter was not measured in our study and is the main study limitation.…”
Section: Discussionmentioning
confidence: 66%
“…One potential mechanism for hypermethylation-induced silencing is changing the structure of specific binding sites for certain transcriptional regulators (24). Epigenetic silencing of genes by promoter hypermethylation is associated with the loss of tumor suppression, increasing tumor severity and reducing patient survival (25). The present meta-analysis revealed significant changes in the methylation status of the CDKN2A, CDKN2B, ID4, GliPR1, p73 and Wilms' tumor 1 (WT1) genes in the major types of leukemia (21,23,(26)(27)(28).…”
Section: Discussionmentioning
confidence: 99%
“…SAV1 contains two WW domains and a SARAH domain in the C-terminal region [38]. RASSF family contains 10 members, namely RASSF1 to RASSF10 [39,40]. RASSF5 is also known as new Ras effector 1 (NORE1) and regulator for cell adhesion and polarization enriched in lymphoid tissues (RAPL).…”
Section: Core Kinase Cascadementioning
confidence: 99%